Construction of novel optical imaging probes and their applications in bioassays - Shao, Qing (2014)
Benefited from the direct and non-invasive visualization, optical imaging has been extensively used for real-time observation of subcellular events and biochemical processes in living systems. In this technology, well-designed imaging probes are required to report the interested biological events with efficient signal contrast and specific target recognition. In this thesis, the author describes the development of novel optical imaging probes for detection of specific biological targets (e.g. bacterial β-lactamase, antibiotic resistant bacteria and reporter enzyme firefly luciferase). Construction of these probes relies on characteristic biological reactions to ensure signal specificity, also involves particular strategies to confer these probes with attractive properties such as covalent labeling activity, photosensitizing capability or spatiotemporal control. Chapter 2 presents enzyme responsive covalent probes for imaging and fast screening of antibiotic resistant bacteria. These probes are designed as pre-quenched. They are activated by endogenous β-lactamase, a resistance-related bacterial enzyme, to generate the fluorescent protein labeling. The covalent labeling property can reduce the fluorescence background by minimizing probe diffusion, thus provides quantitative analysis of the resistant bacterial population (down to as low as 5%) by flow cytometry, also allows single-cell detection and direct observation of bacterial enzyme activity in resistant pathogenic species. Chapter 3 describes the construction of a luminescent Ru(II) probe for intracellular imaging and lethal photosensitization of drug resistant bacteria. By combining enzyme recognizing specificity and photosensitizing function, this probe displays promising imaging and photokilling capabilities to the drug resistant strains, including pathogenic species like clinically isolated methicillin-resistant Staphylococcus aureus. Chapter 4 presents the preliminary results of an ongoing study on the development of fluorescent probes for detection and identification of bacterial β-lactamases through the approach of activity-based protein labeling. Chapter 5 presents the photocaged bioluminescent probes for selective imaging of firefly luciferase reporter gene expression in living mice with simple and controlled photoactivation. With the photocage strategy, the firefly bioluminescence can provide great opportunities for monitoring biological events in vivo with spatial and temporal control.